2011
DOI: 10.1007/s00404-011-2189-y
|View full text |Cite
|
Sign up to set email alerts
|

Right endometrioma is related with more extensive obliteration of the Douglas pouch

Abstract: Moreover, we also showed that in women with a right endometrioma, incidence of the pouch of Douglas obliteration is higher and the endometriosis tends to be more severe compared to women with a left endometrioma. Our most relevant observation is obliteration of Douglas pouch which was found to be more extensive in women with right ovarian endometrioma. Our results showing left lateral predisposition of endometriomas are in agreement with the previous reports and highlight the retrograde menstruation theory for… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
9
1

Year Published

2013
2013
2017
2017

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 18 publications
(11 citation statements)
references
References 19 publications
(24 reference statements)
1
9
1
Order By: Relevance
“…In the absence of specialized ultrasound for prediction of obliteration of the pouch of Douglas (POD), TVS markers for endometriosis, such as ovarian fixation and ovarian endometrioma, may be useful in determining the risk of POD obliteration preoperatively. Ulukus et al . published a study including 340 women with benign ovarian cysts to determine whether laterality of endometriomas was related to severity of endometriosis, and found that women with right‐sided endometrioma had a significantly higher rate of POD obliteration than had women with left‐sided endometrioma (21% vs 6%).…”
Section: Discussionmentioning
confidence: 99%
“…In the absence of specialized ultrasound for prediction of obliteration of the pouch of Douglas (POD), TVS markers for endometriosis, such as ovarian fixation and ovarian endometrioma, may be useful in determining the risk of POD obliteration preoperatively. Ulukus et al . published a study including 340 women with benign ovarian cysts to determine whether laterality of endometriomas was related to severity of endometriosis, and found that women with right‐sided endometrioma had a significantly higher rate of POD obliteration than had women with left‐sided endometrioma (21% vs 6%).…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have demonstrated that endometriomata are significantly associated with both posterior compartment DIE and POD obliteration . In the study by Kondo et al ( n = 201), ovarian endometrioma was significantly associated with the presence of posterior compartment DIE (98.2%; p = 0.01) and intestinal DIE (57.1%, p = 0.01).…”
Section: Discussionmentioning
confidence: 87%
“…posterior compartment DIE nodule, right ovarian fixation, and negative TVS “sliding sign”) were selected, as these were the most significantly associated univariate preoperative features for POD obliteration prediction as determined by logistic regression analysis. The POD2 model differed from POD1 model in combining unilateral ovarian fixation and unilateral ovarian endometrioma with the negative “sliding sign.” These two ovarian features were chosen based on previously published research indicating that ovarian fixation is significantly associated with the presence of endometriosis , as is the presence of ovarian endometrioma with posterior compartment DIE and POD obliteration . Unilateral/bilateral ovarian fixation and ovarian endometrioma were also significantly associated with POD obliteration in the logistic regression analysis.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations